Prevalence and incidence of asthma among underprivileged children in polluted urban areas of India: a childhood asthma intervention and referrals study - Fofani, Nikunj; Markandeywar, Neeraj; Desai, Shripad (International Journal Of Community Medicine And Public Health, 2018)
Background: Childhood asthma has emerged as an important public health issue which is often under diagnosed or undertreated, especially in underprivileged children from slum communities in India. This study aims to increase awareness and facilitate early diagnosis and treatment of childhood asthma. Methods: Americares India Foundation organized 167 asthma screening camps in the city of Bengaluru, Bhubaneswar, Cochin, Lucknow and Nagpur in India from August to November 2016. A total of 10,017 underprivileged children aged ≤16 years were screened for asthma; symptomatic treatment was provided else the children were referred for further investigations and treatment. The camps were organized in collaboration with St. Philomena’s Hospital, Bengaluru; Lourdes Hospital, Cochin; Indian Institute of Public Health, Bhubaneswar; Lata Mangeshkar Hospital, Nagpur; and St. Mary’s Polyclinic, Lucknow. Results: New and known cases of asthma were diagnosed in 199 and 166 children, respectively. The prevalence of asthma was found to be 2.7% in Bhubaneswar, 3.7% in Bengaluru and Lucknow, 3.9% in Cochin and 4.3% in Nagpur. Conclusions: Due to increase in the prevalence of childhood asthma in India, it is important to create awareness and communicate with families/caregivers about asthma and related disorders.